2006
DOI: 10.2166/wpt.2006.046
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Packing Materials in On-Site Wastewater Treatment System

Abstract: Numerous biological, physical and chemical parameters are involved in retention and removal of chemical pollutant and bacteria in wastewater treatment systems. Biofilm presence was often cited for its influence in these mechanisms. Sandy soil is the most used packing material in wastewater treatment study and little information is available for the other soil. The objectives of this study were to compare purification efficiency of packing materials (soil) and to allow a better understanding in purification mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Their characterization confirmed their potential to be used as filtration media [11], since the equivalent diameter, the uniformity coefficient, the porosity and the permeability were in the ranges 0.09-0.14 mm, 1.57-2.60, 38-57% and 0.13-0.41 m/h respectively, showing that sand size can be characterized as thin to medium. Physicochemical (Table 1) and chemical (Table 2) characterization of the sand of dunes showed that the characteristics of all the considered quarries were close to those reported in the available literature [8,9,12,13]. It should only be noted high salinity and carbonate values for some quarries: Temacine quarry for salinity, Guemar and El Oued quarries for carbonate values.…”
Section: Characterization Of the Sand Of Dunesupporting
confidence: 75%
“…Their characterization confirmed their potential to be used as filtration media [11], since the equivalent diameter, the uniformity coefficient, the porosity and the permeability were in the ranges 0.09-0.14 mm, 1.57-2.60, 38-57% and 0.13-0.41 m/h respectively, showing that sand size can be characterized as thin to medium. Physicochemical (Table 1) and chemical (Table 2) characterization of the sand of dunes showed that the characteristics of all the considered quarries were close to those reported in the available literature [8,9,12,13]. It should only be noted high salinity and carbonate values for some quarries: Temacine quarry for salinity, Guemar and El Oued quarries for carbonate values.…”
Section: Characterization Of the Sand Of Dunesupporting
confidence: 75%
“…Wastewater treatment reactors were packed with sand as previously described (Chabaud et al 2006a) and supplied with septic effluent at a nominal load (5 cm/d) and an overload (12 cm/d) corresponding to reactor 1 and 2 respectively (Chabaud et al 2006a). Sand samples (10 cm depth) were removed from the two experimental on-site wastewater treatment reactors and septic effluent, as well as treated effluent were collected.…”
Section: Samplementioning
confidence: 99%
“…In this system, the main removal pollution mechanisms are filtration, adsorption and aerobic degradation by microorganisms arranged in biofilm (Chabaud et al 2006a). The biofilm development in the first centimetres of sand media contributes to the development of clogging zones altering the purification efficiency in soil infiltration treatment system (Stevik et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The renewed interest in ODWT plants is due to their simplicity of implementation, affordability and efficiency. ODWT plants demonstrate very good performance in treating total organic carbon and ammonia nitrogen (N-NH 4 ) as well as in dealing with suspended solids (SS) (Beal et al, 2005;Chabaud et al, 2006a;Maillard, 1998;Siegrist et al, 2000).…”
Section: Context and Objectivesmentioning
confidence: 99%
“…Numerous studies have been carried out concerning SFVDF systems in the field of ODWT in order to determine their behaviour and the characteristics of the materials to be used in order to obtain good sewage treatment performance (Bruen and Piluk, 1994;Chabaud et al, 2006a;Charles et al, 2005;Jayarathne et al, 2007;Jenssen and Siegrist, 1990;Rolland, 2009;Wanko et al, 2005;Whitehead and Geary, 2000).…”
Section: Context and Objectivesmentioning
confidence: 99%